2002
DOI: 10.1007/bf03017900
|View full text |Cite
|
Sign up to set email alerts
|

The Panomat® P-10 micro-volumetric infusion pump is suitable for continuous drug administration at minimal flow rates

Abstract: P Pu ur rp po os se e: : To evaluate the performance of the Panomat® P-10 micro-volumetric infusion pump for its use in drug administration at minimal flow rates (µL·hr -1 ; e.g., intrathecal application).M Me et th ho od ds s: : Fluid delivery at steady state conditions, and after vertical displacement of the syringe pump by -50 cm was determined gravimetrically. The Panomat® P-10 infusion pump was evaluated at 4, 10, 20, 50 and 100 µL·hr -1 , and compared to a conventional syringe pump assembly at 100, 200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In addition, based on these experimental results, a more realistic control firmware that supports various flow rate adjustments and bolus modes will be developed in a further study. (6,7). In contrast, in an implantable device, the altitude difference is relatively small and does not change steeply after implantation.…”
Section: Won Nam Et Almentioning
confidence: 92%
“…In addition, based on these experimental results, a more realistic control firmware that supports various flow rate adjustments and bolus modes will be developed in a further study. (6,7). In contrast, in an implantable device, the altitude difference is relatively small and does not change steeply after implantation.…”
Section: Won Nam Et Almentioning
confidence: 92%
“…To determine the effects of the vertical altitude difference between the drug chamber and the distal end of the outlet catheter, the target injection rate was set at 0.5, 1.0, 1.5, and 2.0 ml/h, respectively, the drug chamber was abruptly dropped 50 cm under the catheter-attached needle, and the retrograde aspiration volume (RAV), zero-drug delivery time (ZDDT), and time to re-establish a 95 per cent steady-state flow were measured. The drug chamber was then abruptly raised 50 cm upwards and the release of an infusion bolus (IB) and the pattern of the actual flowrate in the same operation modes were measured [5, 7]. A patient monitor (DS-5300W; Fukuda Denshi Co. Ltd, Tokyo, Japan) and a data acquisition board (NI-USB 6250; National Instruments Corp., Austin, Texas, USA) were used to extract the information on the internal pressure of the drug chamber.…”
Section: Methodsmentioning
confidence: 99%
“…12 Neff et al reported a reduced gravimetric influence of the Panomat® P-10 (Disetronic Medical Systems AG, Burgdorf, Switzerland) micro-volumetric infusion pump during vertical pump displacement, which was designed especially for microinfusion. 13 Although 50-mL syringes are commonly used when administering catecholamines, we chose 20-mL syringes, which are of relatively low compliance. We use 20-mL syringes in caring for neonates to improve accuracy of drug delivery when infusing catecholamines.…”
Section: Methodsmentioning
confidence: 99%